Submarine Adventure Supplementary Reading Material - Roderick Hunt (Oxford Reading Tree, 2012)
This book is called Submarine Adventure. It's published by Oxford Reading Tree and has a book band of Turquoise. It's part of our Reading Chest library of books to rent.